Genetic and fossil evidence for the origin of modern humans - Stringer, C B; Andrews, P (Science, 1988)
The origin of living Homo sapiens has once again been the subject of much debate. Genetic data on present human population relationships and data from the Pleistocene fossil hominid record are used to compare two contrasting models for the origin of modern humans. Both genetics and paleontology support a recent African origin for modern humans rather than a long period of multiregional evolution accompanied by gene flow.
Keywords: Animals; Paleontology; biologická evoluce; China; Československo; Afrika; lidé; Haplorhini; Skull; Haplorrhini; Fossils; Africa; paleontologie; zkameněliny; Čína; lebka; zvířata; Biological Evolution; Czechoslovakia; Humans